Ekonomi Perspektif Imam al-Shatibi - Zainil Ghulam (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
Development of Islamic Economic Thought has begun since Muhammad SAW was appointed as Rasulullah (messanger of God). Muhammad SAW has issued a number of policies that concerning various matters was related with social matters, in addition is legal issues (fiqh), politics (siyasah), as well as commercial or economic matters (muamalah). The economic problems of the people are part of concerning of the Prophet SAW, because economic problems are the pillars of the faith which must be observed. Furthermore, the policies of the Prophet Muhammad SAW made the guidelines by the Caliphs as their successors in deciding economic issues. Al-Qur'an and Al-Hadith used as the basis of economic theory by the caliphs are also used by his followers in organizing the economic life of the country. Islamic economic thinking is the response of Muslim thinkers to the economic challenges of their time. The Islamic economic thought is inspired and guided by the teachings of the Qur'an and Sunnah as well by their ijtihad (thought) and empirical experience. Ijtihad is a process of humanity, but the teachings of the Qur'an and sunna are not human thoughts. The object of study in Islamic economic thought is not the Qur'anic and Sunnah teachings about economics but the Islamic scholars think about the economy in history or how they understand the teachings of the Qur'an and Sunnah about economics. The object of Islamic economic thought also includes how Islamic economic history takes place in historical practice. Discourse of economic history in Islam in now, was less respond because most of Muslim scholars have studied and conceptualize in such a way. They are the conceptors of Islamic economics actuallya, although the Islamic economic term in Indonesia has only grown rapidly in the last three decades. The study of Islamic economics gradually developed as an interdisciplinary field of science which is the subject of study of fuqaha, mufassir, philosopher, sociologist, and politician. Keywords: ekonomi, al-shatibi, maqasid al-shari'ah